Implicit and Explicit Evaluation: A Brief Review of the Associative-Propositional Evaluation Model - Gawronski, Bertram; Bodenhausen, Galen V. (Social and personality psychology compass, 2014)
A central theme in contemporary psychology is the distinction between implicit and explicit evaluation. Research has shown various dissociations between the two kinds of evaluations, including different antecedents, different consequences, and discrepant evaluations of the same object. The current article provides a brief review of the associative–propositional evaluation (APE) model, which accounts for these dissociations by conceptualizing implicit and explicit evaluations as the behavioral outcomes of two functionally distinct, yet mutually interacting, mental processes. Whereas implicit evaluations are assumed to be the outcome of associative processes, explicit evaluations are conceptualized as the outcome of propositional processes. Associative processes determine the activation of mental contents on the basis of feature similarity and spatiotemporal contiguity; propositional processes involve the validation of activated mental contents on the basis of cognitive consistency. The APE model includes specific assumptions about mutual interactions between the two processes, implying precise predictions about converging versus diverging patterns of implicit and explicit evaluation.